Analisis Keputusan Menggunakan Pendekatan Model Causal Loop Diagram (CLD) Model Dinamik untuk Perencanaan Wisata Syariah Berkelanjutan - Herman Mawengkang; Sutarman; Husain (Institute of Computer Science (IOCS), 2020)
Sustainable tourism development impacts on many factors, so that a dynamic model approach to tourism research becomes clear in many cases, one of which is in the development of Islamic sustainable tourism. These approaches usually look at a particular problem or the whole picture of tourism. As a result, it becomes difficult to manage tourism towards sustainability. This paper provides an overview of the systems thinking approach to systems analysis using the Causal Loop Diagram (CLD) model for sustainable Islamic tourism planning problems. This study shows that systems thinking has proven to be an effective and powerful tool for explaining the complexity of the tourism system. This has helped simplify, clarify and integrate isolated problems associated with the industry, and provided a mechanism for group learning and decision making to achieve desired results. This paper proposes systems thinking to be used as an appropriate tool for sustainable tourism development. The results of this study can describe the dynamic model of sharia tourism development with the CLD approach so that it can see the influencing factors that indicate causation. Keywords: Model Causal Loop Diagram, Dynamic, Tourism, sharia